Beneath the Surface: Identifying Subsurface Caves in "Gua Pandan" Using Integrated Electrical Profiling Method - Antosia, Risky Martin; Akbar, Hendra Hidayat; Santoso, Nono Agus; Putri, Intan Andriani; Farishi, Bilal Al; Natalia, Happy Christin (POSITRON, 2023)
One of the geopark tourism areas in East Lampung Regency, "Gua Pandan," has run into rock subsidence on the surface. As part of the subsidence prevention, indirect electrical methods between resistivity and chargeability profiling were applied to identify the presence of a subsurface cave in the study area. Two measurement lines were carried out with Wenner Alpha and Wenner Schlumberger arrays. Because the depth target is shallow (approximately 10 m) and to obtain a better resolution, each line has a stretch length of 70 m and 2 m electrode spacing. A line was measured over a known underground cave to produce a desired outcome, and the other was in an area with no cavities. Based on the results from each profile of resistivity and chargeability, an air-filled target has a value of over 5,000  and under 6 ms, respectively. Then, integrated processing of both methods generated a metal factor (MF) profile to view the presence and estimated shape of the cave/ cavities. The result represents that an MF value under 1.5 ms/Ωm is a cavity, and solid rock is over 1.5 ms/Ωm. Also, the MF level from both configurations delineates a similar section. However, a modest difference occurs in estimating the cavity shape geometry,  for Wenner Apha and  for Wenner Schlumberger. Furthermore, this study can be an initial step in safety assessment in the area.